2010
DOI: 10.1007/s11745-010-3457-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiling Reveals Tissue‐Specific Differences for Ethanolamide Lipids in Mice Lacking Fatty Acid Amide Hydrolase

Abstract: N-Acylethanolamines (NAE) are fatty acid derivatives, some of which function as endocannabinoids in mammals. NAE metabolism involves common (phosphatidylethanolamines, PEs) and uncommon (N-acylphosphatidylethanolamines, NAPEs) membrane phospholipids. Here we have identified and quantified more than a hundred metabolites in the NAE/endocannabinoid pathway in mouse brain and heart tissues, including many previously unreported molecular species of NAPE. We found that brain tissue of mice lacking fatty acid amide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…A total lipid extract from 100 mg brain, which is an extremely lipid‐rich tissue, would have to be diluted in a volume of 10 mL or more for routine lipidomic analysis. While other analytical methods applied to NAPE skip extensive sample preparation methods 6, 7, 30, 32, 34, the presented sample cleanup by SPE eliminates many highly abundant lipid classes such as triacylglycerols that consequently enables reconstitution of the NAPE‐containing fraction in a much smaller volume (200 μL). Preliminary testing during method development showed no analyte losses caused by SPE sample preparation.…”
Section: Resultsmentioning
confidence: 99%
“…A total lipid extract from 100 mg brain, which is an extremely lipid‐rich tissue, would have to be diluted in a volume of 10 mL or more for routine lipidomic analysis. While other analytical methods applied to NAPE skip extensive sample preparation methods 6, 7, 30, 32, 34, the presented sample cleanup by SPE eliminates many highly abundant lipid classes such as triacylglycerols that consequently enables reconstitution of the NAPE‐containing fraction in a much smaller volume (200 μL). Preliminary testing during method development showed no analyte losses caused by SPE sample preparation.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies have reported changes in NAE and NAT lipids in rodents with pharmacological or genetic disruptions of FAAH ( 6,12,17,18,24,25 ). Most of these reports focus on a single or select number of tissues, and few, if any, have compared acute versus chronic disruption of FAAH in a quantitative manner.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of NAE 16:0 and 18:1 were higher in the DBA/2 heart when compared to other mouse strains,31,32 however, lower levels of NAE 20:4 were measured. Brain levels of all NAEs were lower in the DBA/2 mice when compared to other mouse strains and species 31,33. Very low basal levels of NAE 18:2 have been reported in the brain at ~2 pmol/g FW34 and were not detected in this study.…”
Section: Discussionmentioning
confidence: 60%